Pilot Study on Delay Factors and Solutions Strategies in Government Buildings Projects in Kuwait: Stakeholders’ Perspectives Using Confirmatory Factor Analysis (CFA) - Mubarak M. Aldammak; Noraini Binti Hamzah; Muhamad Azry Khoiry (Buildings)
Construction delays are a repeated problem in government buildings projects in Kuwait, always leading to increased costs and schedule slippage. This pilot study investigates key delay factors and corresponding solutions strategies by analyzing the responses from 60 construction professionals representing project management consultants (PMCs), contractors, and consultants. Using a structured questionnaire and confirmatory factor analysis (CFA), the study identifies and validates critical delay constructs and explores useful solutions measures from stakeholders’ perspectives. The findings provide foundational data to refine the main study and enhance model validity for structural equation modeling (SEM). The top of the delay factors are poor contractor monitoring, weakness of consultant project management team, and design faults. Recommended solutions strategies include establishing a monitoring system to track subcontractor progress and addressing potential delays proactively, ensuring timely approval for the required workforce, and establishing clear delivery schedules. The results validate the questionnaire’s reliability (Cronbach’s alpha = 0.920) and provide insights into urgency areas for delay mitigation in the Kuwaiti governmental building construction sector.